The Attitude of the Language of Ex-Combatans and the Victims of Armed Conflict of Aceh Post-MoU Helsinki - Sanusi, Sanusi; Azwardi, Azwardi; Yusuf, Rusli; Iqbal, Muhammad (Jurnal Ilmiah Peuradeun, 2018)
This study aims to describe the attitude of ex-combatants and conflict victim of Aceh post-MoU Helsinki to the use of language, both Indonesian as a national language and Acehnese as one of the dominant regional languages in Aceh. This project is done within the purpose of Indonesian guidance, protection and defense as the language of unity and language of Aceh as one of the mother tongues in the archipelago. The targets of the annual achievements of this research are as follows: (1) scientific publications, both accredited national scientific journals and international scientific journals, (2) papers in scientific meetings, and (3) ISBN textbooks. The result of the research showed that the attitude of the ex-combatants in the post-MoU Helsinki was positively conflicting, both to the Indonesian language as the national and the Acehnese language as one of the regional languages in Aceh.